Visual sensitivity to color errors in images of natural scenes - Aldaba, Mikel A. (2006)
Simple color-difference formulae and pictorial images have traditionally been used to estimate the visual impact of color errors introduced by image-reproduction processes. But the limited gamut of RGB cameras constrains such analyses, particularly of natural scenes. The purpose of this work was to estimate visual sensitivity to color errors introduced deliberately into pictures synthesized from hyperspectral images of natural scenes without gamut constraints and to compare discrimination thresholds expressed in CIELAB and S-CIELAB color spaces. From each original image, a set of approximate images with variable color errors were generated and displayed on a calibrated RGB color monitor. The threshold for perceptibility of the errors was determined in a paired-comparison experiment. In agreement with previous studies, it was found that discrimination between original and approximate images needed on average a CIELAB color difference ΔE ab * of about 2.2. Although a large variation of performance across the nine images tested was found when errors were expressed in CIELAB units, little variation was obtained when they were expressed in S-CIELAB units.